2008
DOI: 10.1080/09718923.2008.11892628
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Ability Levels and Effectiveness of Problem-Solving Instructional Strategy

Abstract: The paper investigated the impact of problem-solving instructional strategy on the performances of students of different ability levels in Chemistry. The performances of students in the high, medium and low ability levels in a problem-solving task were compared after exposing them to teacher-directed problem-solving instruction. It was detected that there was no significant difference (P>0.05) in the performance of students in the different ability levels after the treatment. Method of instruction was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
(8 reference statements)
5
12
1
2
Order By: Relevance
“…In addition, this instruction can facilitate all students' learning of science, not just the learning of high prior-knowledge students. Similar suggestions can also be found in previous studies of science teaching on argumentation and inquiry (Adesoji, 2008;Cuevas et al, 2005;Yerrick, 2000;Yu et al, 2010;Zohar & Dori, 2003). The other suggestion we would like to address is that the collaborative learning strategies may enhance students' argumentation and inquiry ability.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition, this instruction can facilitate all students' learning of science, not just the learning of high prior-knowledge students. Similar suggestions can also be found in previous studies of science teaching on argumentation and inquiry (Adesoji, 2008;Cuevas et al, 2005;Yerrick, 2000;Yu et al, 2010;Zohar & Dori, 2003). The other suggestion we would like to address is that the collaborative learning strategies may enhance students' argumentation and inquiry ability.…”
Section: Discussionmentioning
confidence: 56%
“…However, the difference in inquiry performance between these two groups was insignificant for Topics 5 and 6, implying that the low prior-knowledge students progressed in their inquiry ability under the online science learning program. Thus, low prior-knowledge students have the potential to perform similar with or better than high prior-knowledge students in scientific inquiry tasks (Adesoji, 2008;Cuevas et al, 2005;Yu et al, 2010).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is, for example, a substantial body of literature on the successful introduction of constructivist approaches to science education into Nigerian classrooms (e.g. Adesoji, 1995Adesoji, , 1997Agbayewa, 1996;Akinbobola, 2004;Folashade and Akinbobola, 2009).…”
Section: Gramsci Explains On the Basis Of What Marx Wrote In The Holymentioning
confidence: 98%
“…A laboratory-based instructional intervention in Physics that combines both problem solving skills, mathematical skills (such as measurement, ratio, proportion) and attitude to laboratory work is likely to improve performance in Physics of low performing students. Adesoji (2008) investigated students' ability levels and effectiveness of problem-solving instructional strategy. He reported that there is disparity in the ability to perform specific tasks.…”
Section: Literature Surveymentioning
confidence: 99%